Regioselective Enzymatic β‐Carboxylation of para‐Hydroxy‐ styrene Derivatives Catalyzed by Phenolic Acid Decarboxylases. Issue 8 (2nd April 2015) - Wuensch, Christiane; Pavkov‐Keller, Tea; Steinkellner, Georg; Gross, Johannes; Fuchs, Michael; Hromic, Altijana; Lyskowski, Andrzej; Fauland, Kerstin; Gruber, Karl; Glueck, Silvia M.; Faber, Kurt
Abstract: We report on a 'green' method for the utilization of carbon dioxide as C1 unit for the regioselective synthesis of ( E )‐cinnamic acids via regioselective enzymatic carboxylation of para ‐hydroxystyrenes. Phenolic acid decarboxylases from bacterial sources catalyzed the β‐carboxylation of para ‐hydroxystyrene derivatives with excellent regio‐ and ( E / Z )‐stereoselectivity by exclusively acting at the β‐carbon atom of the C=C side chain to furnish the corresponding ( E )‐cinnamic acid derivatives in up to 40% conversion at the expense of bicarbonate as carbon dioxide source. Studies on the substrate scope of this strategy are presented and a catalytic mechanism is proposed based on molecular modelling studies supported by mutagenesis of amino acid residues in the active site. Abstract :